Approved Annual Plan 1983-84 (Statements GN- 1 to 6) Haryana State - Planning Commission (Planning Commission, 1983)
Annual Plan (1983-84) Consolidated Statement (Major Head Wise)Outlay and Expenditure Annual Plan (1983-84) Head Sub-Head of Development Outlay and Expenditure Development Schemes/Projects Outlay and Expenditure Research and Education (Agricultural University) Agriculture(Crop Husbandry) Development Schemes/Projects Outlay and Expenditure Special Projects for Rural Development (Agriculture and Revenue Department) Marketing, Storage and Warehousing (Agriculture Department) Land Reforms (Consolidation of Holdings) Minor Irrigation Soil and Water Conservation.
Planning Department, Government of Haryana